The relationship between organizational justice and employees' job satisfaction at UiTM Pahang Branch, Jengka Campus / Nurul Jannah Amiruddin - Amiruddin, Nurul Jannah (Faculty of Business and Management, 2020)
The purpose of this study is to examine the relationship between Organizational Justice and Employees' Job Satisfaction at UiTM Pahang Branch, Jengka Campus. The objective of this study is to analyze the level of organizational justice and job satisfaction of employees at UiTM Pahang Branch, Jengka Campus and to identify the relationship between organizational justice and job satisfaction as perceived by the employees of UiTM Pahang Branch, Jengka Campus. Besides that, 200 questionnaires have been distributed to randomly selected non-academic employees working at UiTM Pahang Branch, Jengka Campus to achieve the objectives of this study. All the data collected are analysed using SPSS Version 25 program. The finding suggests that there is a moderate relationship between organizational justice and employees' job satisfaction at UiTM Pahang Branch, Jengka Campus.